Risk factors of nocturnal enuresis among school-going children of 6–15 years in a selected Upazila of Bangladesh - Hossain, M. Iqbal; Yasmin, Rumana; Fardous, Jannatul; Chakma, Pampi; Billah, M. Masum; Ashraf, Rezwana; Alam, M. Kabir; Khan, M. Anwar Hossain (International Journal of Contemporary Pediatrics, 2026)
Background: Nocturnal enuresis, or bedwetting, is a common condition among children aged five years and older, with potential psychosocial impacts such as low self-esteem, social anxiety, and disrupted family dynamics. Both genetic and environmental factors, including bladder dysfunction, sleep disturbances, stress, and lifestyle habits, contribute to its occurrence. In Bangladesh, data on risk factors for nocturnal enuresis among school-aged children are limited. To identify and analyze the risk factors associated with nocturnal enuresis among school-going children aged 6–15 years in Rupganj Upazila, Narayanganj, Bangladesh. Methods: A cross-sectional analytical study was conducted among 384 school-going children aged 6–15 years from January 2022 to September 2023. Data on demographics, lifestyle, medical history and indirect evidence of urinary tract infection (UTI) were collected through structured questionnaires, anthropometric measurements, and dipstick urinalysis. Associations were assessed using Chi-square or Fisher’s exact test, and risk factors were analyzed using univariate and multivariate logistic regression. Statistical significance was set at p<0.05. Results: Among participants, number of enuretic children decreases with age. In multivariate analysis, significant predictors of nocturnal enuresis included younger age (6–7 years, OR=6.536), stressful events (OR=8.033), lower urinary tract symptoms (OR=27.643), sleep disturbances (OR=36.571), and drinking more fluids in the evening (OR=10.940). Family history, constipation, obesity, pinworm infestation and/or anal itching, and caffeinated drinks were significant in univariate analysis but not in multivariate models. Positive leukocyte esterase tests, indicating possible UTI, were more common in enuretic children. Conclusion: Nocturnal enuresis in school-aged children is influenced by a combination of behavioral, physiological, and environmental factors. Early identification of significant predictors, such as stress, LUTS, sleep disturbance, and higher evening fluid intake, can guide targeted interventions to reduce the prevalence and psychosocial impact of enuresis in this population.